Induction of apoptosis in cervical and breast cancer cells using quinoxaline derivatives - Satekge, Tebogo Yvette (My University, 2024)
Background: Cervical and breast cancers remain a public health concern in South Africa with an increasing rate of incidences and mortalities globally. Current treatment options are not only costly but also present undesirable side effects, induce multidrug resistance, and result in high rates of cancer remissions. To limit cancer recurrences, the focus of anticancer drug development has been on increasing sensitivity of cancer cells to drug-induced apoptosis as a prospective cancer therapy. Apoptosis and its associated cancer hallmarks are the gold standard targets for the development of conventional cancer treatment strategies for management of cancers. In view of current challenges encountered in cancer treatment options, more target-specific, less costly, and highly effective inducers of apoptosis are urgently required. Quinoxaline derivatives are synthetic small molecules that hold a plethora of desirable biological activities with their structures being constantly modified to improve their therapeutic target specificity, response rate, and accessibility. Aim of study: Hence, this study primarily aimed at investigating the ability of selected novel quinoxaline derivatives to induce apoptotic cell death in cervical cancer (CaSki) and breast cancer (MCF-7) cells. Methods: To achieve this aim, characterisation of the quinoxaline derivatives, LAM21D and LAM29A, was performed to determine the UV-Vis absorption spectrum utilising the UV/Vis spectrophotometer. The antioxidant potential of the quinoxaline derivatives was evaluated using the ferric reducing antioxidant power (FRAP) assay and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay while the total phenolic content was determined using the Folin Ciocalteu’s total phenolic content assay. The ability of quinoxaline derivatives to inhibit the viability of CaSki cervical and MCF-7 breast cancer cells was assessed using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay. The effect of the derivatives on morphological features of the described cancer cells was captured and analysed using the Ti-E inverted microscope and apoptosis induced by the derivatives was quantified using the Muse™ Annexin-V and dead cell assay. The effect of quinoxaline derivatives on ROS production in the cells was established using Muse™ oxidative stress assay. The Muse™ Ki67 proliferation assay was carried out to measure Ki67 expression levels which correlates with the proliferation percentages in CaSki cells. The Muse™ cell cycle assay was performed to evaluate the effect of quinoxaline derivatives on cell cycle progression. The CB-Dock and SwissADME web-based softwares were used to evaluate the binding patterns of quinoxaline derivative LAM-21D and its drug-likeness propensity. Results: Preliminary screening showed that LAM-21D exerted high selectivity towards CaSki cells at 250 μM with minimal cytotoxicity on the noncancerous HEK-293 cells while LAM-29A exhibited high selectivity towards MCF-7 cells. However, although LAM-21D induced apoptosis in CaSki cells, LAM-29A did not induce apoptosis in MCF-7 cells. As a result, assays on downstream pathways were conducted to evaluate the activity of LAM-21D on CaSki cells. A reduction in Ki67 expression which correlated with a reduction in cell proliferation was observed when cells were treated with LAM-21D. There were insignificant changes observed in Ki67 expression when MCF-7 cells were treated with LAM-29A. Both derivatives, LAM-29A and LAM-21D, induced minimal cytotoxicity on the noncancerous cells and LAM-21D significantly reduced Ki67 expression, induced ROS production, S-phase cell cycle arrest, and apoptosis in Caski cervical cancer cells. The In-silico studies revealed an interaction of the compound with the anti- apoptotic BCL-2 protein and p65 NF-κB transcription factor. The compound also showed drug-likeness properties as per ADMET studies. Further studies are required to fully delineate the anticancer mechanisms of this compound. Nonetheless, this compound could be a potential candidate to explore in the therapeutic targets for cervical cancer. Structural modifications are recommended on both quinoxaline derivatives to improve their anticancer properties against cervical and breast cancer cells
Thesis (M.Sc. (Biochemistry)) -- University of Limpopo, 2024
Keywords: Induction; Apoptosis; Cervical and Breast Cancer; Cells; Quinoxaline; Apoptosis; Cervix uteri -- Cancer; Breast -- Cancer